Response of Endolithic Chroococcidiopsis Strains From the Polyextreme Atacama Desert to Light Radiation - Casero, María Cristina; Ascaso, Carmen; Quesada, Antonio; Mazur-Marzec, Hanna; Wierzchos, Jacek (Frontiers in Microbiology, 2021)
Cyanobacteria exposed to high solar radiation make use of a series of defense mechanisms, including avoidance, antioxidant systems, and the production of photoprotective compounds such as scytonemin. Two cyanobacterial strains of the genus Chroococcidiopsis from the Atacama Desert – which has one of the highest solar radiation levels on Earth- were examined to determine their capacity to protect themselves from direct photosynthetically active (PAR) and ultraviolet radiation (UVR): the UAM813 strain, originally isolated from a cryptoendolithic microhabitat within halite (NaCl), and UAM816 strain originally isolated from a chasmoendolithic microhabitat within calcite (CaCO3). The oxidative stress induced by exposure to PAR or UVR+PAR was determined to observe their short-term response, as were the long-term scytonemin production, changes in metabolic activity and ultrastructural damage induced. Both strains showed oxidative stress to both types of light radiation. The UAM813 strain showed a lower acclimation capacity than the UAM816 strain, showing an ever-increasing accumulation of reactive oxygen species (ROS) and a smaller accumulation of scytonemin. This would appear to reflect differences in the adaptation strategies followed to meet the demands of their different microhabitats.